Model Pengembangan Hukum Islam Berbasis Kedaerahan: Kajian Terhadap Ijma’ Ahl Al-Madīnah dan Implikasinya - Muhammad Hasan (Ulumuna, 2015)
The basic spirit of Islamic law is s\ālih\un likulli zamān wa makān. Meanwhile, Islamic law delivered by the Prophet Muhammad and developed by his companions, even by Imam of the schools, is still limited to the mindset and culture of Arab society. Therefore, efforts to resolve various issues of Islamic law that arise in different parts of the world need a prototype methodology of thinking so that the Islamic law produces humanist characteristics. This paper offers a study on the development of Islamic law methods by taking a model of ijmā‘ ‘ahl al-Madīnah. In this case, ijmā‘ ‘ahl al-Madīnah is seen as a model of manhaj istinbāt\ of Islamic law on the ground of region. In the present context, in addition to masādir al-ah\kām, ijmā‘ ‘ahl al-Madīnah needs to be positioned as the methodology of Islamic law which results in humanist Islamic legal perspective. Since ijmā‘ ‘ahl al-Madīnah as masādir al-ah\kām has grounded reason then ijmā‘ ‘ahl al-Madīnah as manhaj al-fikr has a logical argument. Its implication is that the consensus (ijmā‘) based on the regional jurisprudence has become a valid method and source of Islamic law. DOI: http://dx.doi.org/10.20414/ujis.v19i1.1255